Challenges in the Contemporary Management of Syphilis among Pregnant Women in New Orleans, LA - Irene A. Stafford; Alexandra Berra; Charles G. Minard; Virginia Fontenot; Rachel H. Kopkin; Eliza Rodrigue; Charles M. Roitsch; Martha W. Rac; James B. Hill (Hindawi Limited, 2019)
Objective. The aim of this retrospective review is to evaluate trends in the management of maternal and congenital syphilis (CS) in a tertiary care center in New Orleans, LA. Study Design. All cases of maternal and neonatal syphilis over a five year period at Touro Infirmary, New Orleans, LA, were identified using ICD-9/10 codes. Charts were reviewed for demographic and obstetrical variables, stage of syphilis at diagnosis, lab values, and treatment regimen. Newborn treatment and other outcomes were recorded. Results. During the study period 106 infected mother-baby pairs were identified. Of these, 73 charts are available for review. 41% (n = 30) of women received inadequate therapy according to their stage of disease. 9% of newborns (n = 6) were found to be symptomatic for CS; however, only 83.3% of these were admitted to the neonatal intensive care unit. Only 20% (n = 6) of infants were adequately treated with an extended penicillin regimen if the mother was not adequately treated. Furthermore, only 63.0% of newborns had a nontreponemal titer performed. Conclusion. With rising rates of CS, strict adherence to the 2015 CDC guidelines for treatment of syphilis must be maintained.